Research Progress on the Mechanism of Itaconate Regulating Macrophage Immunometabolism - Shi, Jia; Cai, Cheng (Frontiers in Immunology, 2022)
The field of immunology is undergoing rapid and dramatic changes. Immunometabolism, a change in metabolic pathways within immune cells, is a key determinant in the activation of immune cells, and intermediates of immunometabolic processes which can influence inflammatory gene expression and play a role in inflammation. Itaconate is one of the most representative metabolites, produced in the tricarboxylic acid cycle (TCA cycle), which links macrophage metabolism, oxidative stress response and immune response to regulate macrophage activity, playing an important role in the function of macrophages. In this paper, we review the mechanisms of the metabolite itaconate and its derivatives in the regulation of macrophage immune metabolism, intending to gain further insight into the role and mechanisms of this metabolite in macrophages and provide new ideas for the mechanisms and treatment of clinical diseases.